Changes of Social Networks during the Covid-19 Pandemic: Who is affected and what are its Consequences for Psychological Strain? - Ariane Bertogg; Sebastian Koos (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2021)
Contact restrictions and distancing measures are among the most effective non-pharmaceutical measures to stop the spread of the SARS-CoV2 virus. Yet, research has only begun to understand the wider social consequences of these interventions. This study investigates how individuals' social networks have changed since the outbreak of the pandemic and how these changes relate to psychological strain. Based on an online survey of the German adult population, four types of change are distinguished: loss, gain, and intensification of ties, as well as pandemic-related conflicts. One in two respondents has experienced at least one of these four changes. Loss is more frequently reported than gain of ties, and intensification occurred more frequently than conflicts. Loss of ties and conflicts are furthermore associated with higher levels of psychological strain.
urn:nbn:de:bsz:352-2-9g2s63b2auth2
Keywords: L14; I31; 320; Network Change; Social Ties; Health Risks; Covid-19